2015
DOI: 10.1007/s11157-015-9379-1
|View full text |Cite
|
Sign up to set email alerts
|

A review on the state-of-the-art of physical/chemical and biological technologies for biogas upgrading

Abstract: 14The lack of tax incentives for biomethane use requires the optimization of both biogas 15 production and upgrading in order to allow the full exploitation of this renewable energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
316
2
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(401 citation statements)
references
References 96 publications
6
316
2
14
Order By: Relevance
“…However, dosing points and recirculating methods are independent. Among different combinations, dosing air in the headspace with liquid recirculation is most frequently used (Muñoz et al, 2015). As mentioned earlier, desulfurization can occur directly into the main digester or in a separate microaerobic compartment.…”
Section: Microaeration Desulfurizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dosing points and recirculating methods are independent. Among different combinations, dosing air in the headspace with liquid recirculation is most frequently used (Muñoz et al, 2015). As mentioned earlier, desulfurization can occur directly into the main digester or in a separate microaerobic compartment.…”
Section: Microaeration Desulfurizationmentioning
confidence: 99%
“…Contrary, when the air/oxygen is bubbled into the liquid phase, a fraction of oxygen is used to oxidize the degradable organic compounds leading to some losses of oxygen. Under such circumstances, higher amounts of air/oxygen need to be dosed into the reactor which would result in an increased possibility of biogas contamination and dilution as discussed earlier In order to determine the proper dosage of air/oxygen injected into the reactor, a ratio in relation to the biogas production (O2 rate/biogas rate) has been proposed by Muñoz et al (2015). They argued that a 0.3-3% O2 rate in relation to biogas production rate is suitable for microaeration.…”
Section: Dosing Pointmentioning
confidence: 99%
“…Bauer et al reported that the investment costs of water scrubbing plants with a capacity of 100 Sm 3 h −1 amounts to 5000 € Sm −3 h, while they linearly decrease from 5000 to 2500 € Sm −3 h when the biogas capacity to be processed increases from 100 to 500 Sm 3 h −1 . Munoz et al reported that the investment costs are in the range of 1800–2000 € Sm −3 h for plant capacities over 1000 Sm 3 h −1 . According to , , , the operating costs range from 0.11 to 0.15 € per 1 Sm 3 biomethane, which are mainly caused by both energy consumption and annual maintenance costs (2–3 % of the investment costs).…”
Section: Biogas Upgrading By Water Scrubbingmentioning
confidence: 99%
“…CO 2 , N 2 , H 2 O, and H 2 S constitute the major contaminants of biogas, since they decrease its specific calorific value. Besides, high levels of H 2 S in combination with condensate H 2 O causes corrosion in compressors, pipelines, gas storage tanks, and engines …”
Section: Introductionmentioning
confidence: 99%